Contemplative practices in higher education : powerful methods to transform teaching and learning - Barbezat, Daniel; Bush, Mirabai, 1939- (San Francisco : Jossey-Bass, a Wiley brand, 2014)
"Contemplative practices are used in just about every discipline--from physics to economics to history--and are found in every type of institution. Each year more and more faculty, education reformers, and leaders of teaching and learning centers seek out best practices in contemplative teaching, and now can find them here, brought to you by two of the foremost leaders and innovators on the subject. This book presents background information and ideas for the practical application of contemplative practices across the academic curriculum from the physical sciences to the humanities and arts. Examples of contemplative techniques included in the book are mindfulness, meditation, yoga, deep listening, contemplative reading and writing, and pilgrimage, including site visits and field trips." -- Publisher's website.
Foreword / by Parker J. Palmer -- Preface -- Acknowledgments -- 1. Transformation and renewal in higher education -- 2. Current research on contemplative practice -- 3. Contemplative pedagogy in practice : two experiences -- 4. Teacher preparation and classroom challenges -- 5. Mindfulness -- 6. Contemplative approaches to reading and writing -- 7. Contemplative senses : deep listening and beholding -- 8. Contemplative movement -- 9. Compassion and loving kindness -- 10. Guest speakers, field trips, and retreats -- 11. Conclusion -- Afterword / by Arthur Zajonc.
Includes bibliographical references (pages 207-215) and index.
Machine generated contents note: Foreword by Parker J. Palmer vii Preface xi Acknowledgments xvii The Authors xxi PART ONE Theoretical and Practical Background 1 1 Transformation and Renewal in Higher Education 3 2 Current Research on Contemplative Practice 21 3 Contemplative Pedagogy in Practice: Two Experiences 39 4 Teacher Preparation and Classroom Challenges 67 PART TWO A Guide to Contemplative Practices 87 Introduction to the Practices 89 5 Mindfulness 95 6 Contemplative Approaches to Reading and Writing 110 7 Contemplative Senses: Deep Listening and Beholding 137 8 Contemplative Movement 159 9 Compassion and Loving Kindness 174 10 Guest Speakers, Field Trips, and Retreats 189 11 Conclusion 198 Afterword by Arthur Zajonc 205 References 207 Index 217 .
Keywords: College teaching -- Philosophy; Reflective teaching; Reflective learning; Transformative learning; Contemplation; EDUCATION / Higher; EDUCATION / Teaching Methods & Materials / General; College teaching -- Philosophy; Contemplation; Reflective learning; Reflective teaching; Transformative learning